Preservation of cassava (Manihot esculenta Crantz): A major crop to nourish people worldwide - Gnonlonfin, G.J.B.; Sanni, A.; Brimer, L. (Wiley, 2012)
This chapter considers the increase in cassava production and processing into a wide range of traditional and improved cassava-based products worldwide. Toxic cyanogenic glycosides are removed from high cyanogenic cassava cultivars by known techniques prior to further processing. Therefore we also discuss the overall detoxification processes and steps as well as the shelf life and end-use of different cassava-based products.